Analisa Peluang dan Tantangan Produk Furniture Kayu Indonesia dalam Perdagangan Internasional dengan Korea Selatan - Fitri Handayani; Daspar (Jurnal Ekonomi dan Bisnis Digital, 2025)
Indonesian wooden furniture has very good potential in the international market, especially with South Korea, which is a country with a trend for high-aesthetic natural material goods.Based on that assessment, this research aims to analyze the opportunities and challenges faced by the Indonesian wooden furniture industry that wants to enter the South Korean market.Through a descriptive qualitative approach and research literature, the authors were able to reach findings that opportunities include raw material sources, unique furniture designs, skilled labor, and the implementation of IK-CEPA.On the other hand, the challenges include labor costs and relevant child labor